Pal Jepang Hill Tourism as a Tourist Attraction in Sapit Village, East Lombok Regency - Prayuda, Danu Satria; Anggartyas, Putu Arya Reksa; Kosala, Made Dayuh Hari (Language Assistance, 2025)
This study investigates the tourism development potential of Pal Japan Hill in Sapit Village, Lombok. Its objectives are to identify and assess natural, cultural, and artificial attractions, determine influencing factors, and formulate development strategies. Utilizing a qualitative methodology, primary data was gathered through observation, in-depth interviews, and focus group discussions (FGD), supplemented by secondary data and documentation. Data analysis employed SWOT analysis. Findings reveal Pal Japan Hill possesses significant and diverse tourism potential across natural, cultural, and artificial domains. Key factors enabling and constraining development were identified. Based on the SWOT analysis, the study proposes a strategic framework to leverage strengths and opportunities, address weaknesses and threats, and guide the sustainable development of Pal Japan Hill as a competitive tourist destination.